2022
DOI: 10.1332/174426421x16390538025881
|View full text |Cite
|
Sign up to set email alerts
|

Evidence-based practice and management-by-knowledge of disability care: rigid constraint or fluid support?

Abstract: Background: Although increasingly accepted in some corners of social work, critics have claimed that evidence-based practice (EBP) methodologies run contrary to local care practices and result in an EBP straitjacket and epistemic injustice. These are serious concerns, especially in relation to already marginalised clients.Aims and objectives: Against the backdrop of criticism against EBP, this study explores the ramifications of the Swedish state-governed knowledge infrastructure, ‘management-by-knowledge’, fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…It has been suggested that acknowledging different ways of understanding EBP among politicians, managers and executive staff can create a conducive EBP atmosphere for realizing social work practices that use both research- and practice-based knowledge (Avby et al , 2014; Gambrill, 2006; Marsh and Fisher, 2008). Social work experience and the influence of colleagues and supervisors are important sources of knowledge (Bergmark and Lundström, 2002; Burton and Chapman, 2004; Horder, 2007; Pistone et al , 2022), suggesting the importance of integrated professional knowledge. Professional learning and knowledge use are important for EBP development (Avby, 2015), including making EBP practical, visible and put into words (Avby, 2018).…”
Section: Implementing Evidence-based Practice In Workplace Practicementioning
confidence: 99%
See 1 more Smart Citation
“…It has been suggested that acknowledging different ways of understanding EBP among politicians, managers and executive staff can create a conducive EBP atmosphere for realizing social work practices that use both research- and practice-based knowledge (Avby et al , 2014; Gambrill, 2006; Marsh and Fisher, 2008). Social work experience and the influence of colleagues and supervisors are important sources of knowledge (Bergmark and Lundström, 2002; Burton and Chapman, 2004; Horder, 2007; Pistone et al , 2022), suggesting the importance of integrated professional knowledge. Professional learning and knowledge use are important for EBP development (Avby, 2015), including making EBP practical, visible and put into words (Avby, 2018).…”
Section: Implementing Evidence-based Practice In Workplace Practicementioning
confidence: 99%
“…seeing social workers as theorists (Burton and Chapman, 2004). However, it is also important to consider both the social workers’ and the service users’ experiences and knowledge and their mutual interaction in social care practices (Pistone et al , 2022). Also, social workers can contribute to OL by developing collaborative networks sharing ideas about different ways to use EBP in social work (Mosley et al , 2019; Chea et al , 2022).…”
Section: Implementing Evidence-based Practice In Workplace Practicementioning
confidence: 99%